Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Mealybug, Planococcus ficus, reduction through pavement ant, Tetramorium immigrans, management using polyacrylamide hydrogel baits in vineyards - Nathan H. Mercer; David R. Haviland; Kent M. Daane (Crop Protection, 2025)

Novel dispensers and variable deployment rates for mating disruption of a vineyard mealybug, Planococcus ficus - Nathan H. Mercer; Jeannine C. Lowrimore; Peter S. McGhee; Thomas R. Martin; Kevin R. Cloonan; Kent M. Daane (Crop Protection, 2023)

Identifying cryptic species of Planococcus infesting vineyards to improve control efforts - Margarita C. G. Correa; Ferran Palero; Vitor C. Pacheco da Silva; M. Bora Kaydan; Jean-Francois Germain; Shaaban Abd-Rabou; Kent M. Daane; Arturo Cocco; Elie Poulin; Thibaut Malausa (Journal of Pest Science, 2023)

Evaluation of egg parasitoid Hadronotus pennsylvanicus as a prospective biocontrol agent of the leaffooted bug Leptoglossus zonatus - Robert K. Straser; Kent M. Daane; Elijah Talamas; Houston Wilson (BioControl, 2022)
The western leaffooted bug, Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae), is a key pest of almonds and pistachios in the USA. With limited monitoring strategies and no economic threshold developed, the use of broad-spectrum insecticides remains the primary control tactic for L. zonatus . In pursuit of more sustainable management options, experiments were carried out to assess the biocontrol potential of the egg parasitoid Hadronotus pennsylvanicus (Ashmead) (Hymenoptera: Scelionidae) against L. zonatus . Biological and demographical attributes of H. pennsylvanicus were evaluated under controlled laboratory conditions. Mated females lived on average 116 days. However, female longevity declined by 74% when provided with host eggs, and by 97% when deprived of a suitable diet. Females produced an average 39.70 offspring, with peak fecundity observed within the first week of their lifespan. The total progeny was on average 92.75% female. Non-reproductive host mortality accounted for > 52% of the total egg mortality observed within the first two weeks, and represented the majority of total host egg mortality thereafter. Age of host eggs did not influence parasitism rates. Under laboratory conditions, H. pennsylvanicus exhibits suitable demographic and reproductive traits as a candidate biocontrol agent of L. zonatus . Further research is needed to determine how to best manipulate and enhance H. pennsylvanicus populations to promote biocontrol of L. zonatus under field conditions.

Irrigated trap crops impact key hemipteran pests in organic pistachio orchard - Judith M. Stahl; Houston Wilson; Robert K. Straser; Jessica J. Maccaro; Kent M. Daane (Arthropod-Plant Interactions, 2021)
Using sown groundcovers as trap crops to protect a cash crop is a traditional pest management tool. Pistachio is a major crop in California’s Central Valley, where high summer temperatures and little to no precipitation between May and November lead to summer dry-down of annual groundcover. Hemipteran pests that consist of ‘small bugs’ and ‘large bugs’ are a major contributor to nut damage, especially in organic production. In this 2-year field study, we tested the use of irrigated trap crop mixtures, sown between tree rows, to reduce those hemipteran pests’ abundance or damage. Biweekly beat samples of the tree canopy and sweep samples of the sown groundcovers in trap crop plots and resident weedy vegetation in control plots were taken over two consecutive growing seasons. Arthropod richness and abundance were highest in the groundcover and tree canopy in the trap crop plots. Small and large bug pest populations were higher and lower, respectively, in the tree canopy in trap crop plots, indicating a mixed response of these hemipterans to the presence of the trap crops. Additionally, natural enemy populations were more abundant in the tree canopy in trap crop plots than in control plots. There was no difference in nut damage between plots with and without the trap crop. These findings suggest that populations of hemipteran pests and beneficials can be manipulated successfully with irrigated trap crops, but future studies will need to focus on doing so in a way that decreases hemipteran pistachio damage.

Potential host ranges of three Asian larval parasitoids of Drosophila suzukii - Kent M. Daane; Xingeng Wang; Brian N. Hogg; Antonio Biondi (Journal of Pest Science, 2021)
Asobara japonica (Hymenoptera: Braconidae), Ganaspis brasiliensis and Leptopilina japonica (Hymenoptera: Figitidae) are Asian larval parasitoids of spotted wing drosophila, Drosophila suzukii (Diptera: Drosophilidae). This study evaluated these parasitoids’ capacity to attack and develop from 24 non-target drosophilid species. Results showed that all three parasitoids were able to parasitize host larvae of multiple non-target species in artificial diet; A. japonica developed from 19 tested host species, regardless of the phylogenetic position of the host species, L. japonica developed from 11 tested species; and G. brasiliensis developed from only four of the exposed species. Success rate of parasitism (i.e., the probability that an adult wasp successfully emerged from a parasitized host) by the two figitid parasitoids was low in hosts other than the three species in the melanogaster group ( D. melanogaster , D. simulans , and D. suzukii ). The failure of the figitids to develop in most of the tested host species appears to correspond with more frequent encapsulation of the parasitoids by the hosts. The results indicate that G. brasiliensis is the most host specific to D. suzukii , L. japonica attacks mainly species in the melanogaster group and A. japonica is a generalist, at least physiologically. Overall, the developmental time of the parasitoids increased with the host’s developmental time. The body size of female A. japonica (as a model species) was positively related to host size, and mature egg load of female wasps increased with female body size. We discuss the use of these parasitoids for classical biological control of D. suzukii .

Host preference of three Asian larval parasitoids to closely related Drosophila species: implications for biological control of Drosophila suzukii - Antonio Biondi; Xingeng Wang; Kent M. Daane (Journal of Pest Science, 2021)

Exploration for native parasitoids of Drosophila suzukii in China reveals a diversity of parasitoid species and narrow host range of the dominant parasitoid - Massimo Giorgini; Xin-Geng Wang; Yan Wang; Fu-Shou Chen; Evelyne Hougardy; Hong-Mei Zhang; Zong-Qi Chen; Hong-Yin Chen; Chen-Xi Liu; Pasquale Cascone; Giorgio Formisano; Gislaine A. Carvalho; et al. (Journal of Pest Science, 2019)

Temperature-dependent development of Oenopia conglobata (Col.: Coccinellidae) fed on Aphis gossypii (Hem.: Aphididae) - Mohammad Amin Jalali; Samane Sakaki; Mahdi Ziaaddini; Kent M. Daane (International Journal of Tropical Insect Science, 2018)

Innate Olfactory Responses of Asobara japonica Toward Fruits Infested by the Invasive Spotted Wing Drosophila - Antonio Biondi; Xingeng Wang; Jeffrey C. Miller; Betsey Miller; Peter W. Shearer; Lucia Zappalà; Gaetano Siscaro; Vaughn W. Walton; Kim A. Hoelmer; Kent M. Daane (Journal of Insect Behavior, 2017)

Disease progression of vector-mediated Grapevine leafroll-associated virus 3 infection of mature plants under commercial vineyard conditions - G. Kai Blaisdell; Monica L. Cooper; Emily J. Kuhn; Katey A. Taylor; Kent M. Daane; Rodrigo P. P. Almeida (European Journal of Plant Pathology, 2016)

Life-history and host preference of Trichopria drosophilae, a pupal parasitoid of spotted wing drosophila - Xin-Geng Wang; Gülay Kaçar; Antonio Biondi; Kent M. Daane (BioControl, 2016)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Population dynamics and ecology of Drosophila suzukii in Central California - Xin-Geng Wang; Thomas J. Stewart; Antonio Biondi; Brandy A. Chavez; Chuck Ingels; Janet Caprile; Joseph A. Grant; Vaughn M. Walton; Kent M. Daane (Journal of Pest Science, 2016)

First exploration of parasitoids of Drosophila suzukii in South Korea as potential classical biological agents - Kent M. Daane; Xin-Geng Wang; Antonio Biondi; Betsey Miller; Jeffrey C. Miller; Helmut Riedl; Peter W. Shearer; Emilio Guerrieri; Massimo Giorgini; Matthew Buffington; Kees van Achterberg; Yoohan Song; et al. (Journal of Pest Science, 2016)

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Classic biological control of olive fruit fly in California, USA: release and recovery of introduced parasitoids - Kent M. Daane; Xingeng Wang; Diego J. Nieto; Charles H. Pickett; Kim A. Hoelmer; Arnaud Blanchet; Marshall W. Johnson (BioControl, 2015)

Brood Guarding by an Adult Parasitoid Reduces Cannibalism of Parasitoid-Attacked Conspecifics by a Caterpillar Host - Xin-Geng Wang; Sean M. Tomajan; Kent M. Daane (Journal of Insect Behavior, 2014)

Sexual communication and related behaviours in Tephritidae: current knowledge and potential applications for Integrated Pest Management - Giovanni Benelli; Kent M. Daane; Angelo Canale; Chang-Ying Niu; Russell H. Messing; Roger I. Vargas (Journal of Pest Science, 2014)

Low temperature storage effects on two olive fruit fly parasitoids - Kent M. Daane; Xin-geng Wang; Marshall W. Johnson; Monica L. Cooper (BioControl, 2013)

Syrphid flies suppress lettuce aphids - Erik H. Nelson; Brian N. Hogg; Nicholas J. Mills; Kent M. Daane (BioControl, 2012)

Erratum to: Establishment of Psyllaephagus parvus and P. perplexus as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

Establishment of Psyllaephagus parvus and P. perplexans as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

Comparative evaluation of two olive fruit fly parasitoids under varying abiotic conditions - Xin-geng Wang; Marshall W. Johnson; Victoria Y. Yokoyama; Charles H. Pickett; Kent M. Daane (BioControl, 2011)

Regional patterns in the invasion success of Cheiracanthium spiders (Miturgidae) in vineyard ecosystems - Brian N. Hogg; Rosemary G. Gillespie; Kent M. Daane (Biological Invasions, 2010)

Identifying the predator complex of Homalodisca vitripennis (Hemiptera: Cicadellidae): a comparative study of the efficacy of an ELISA and PCR gut content assay - Valerie Fournier; James Hagler; Kent Daane; Jesse de León; Russell Groves (Oecologia, 2008)

The biology of Bracon celer as a parasitoid of the olive fruit fly - Karen R. Sime; Kent M. Daane; John W. Andrews; Kim Hoelmer; Charles H. Pickett; Hannah Nadel; Marshall W. Johnson; Russell H. Messing (BioControl, 2006)

(2,3,4,4-Tetramethylcyclopentyl)Methyl Acetate, a Sex Pheromone from the Obscure Mealybug: First Example of a New Structural Class of Monoterpenes - Jocelyn G. Millar; Sharon L. Midland; J. Steven McElfresh; Kent M. Daane (Journal of Chemical Ecology, 2005)